Moment loading of caissons installed in saturated sand - Villalobos, F; Byrne, B; Houlsby, G (2005)
A series of moment capacity tests have been carried out at model scale, to investigate the effects of different installation procedures on the response of suction caisson foundations in sand. Two caissons of different diameters and wall thicknesses, but similar skirt length to diameter ratio, have been tested in watersaturated dense sand. The caissons were installed either by pushing or by using suction. It was found that the moment resistance depends on the method of installation. © 2005 Taylor and Francis Group.